سرطان المرارة - علي, مـاجد; مسعود, سجيع; سلـيمان, يوسـف (Latakia University Journal -Medical Sciences Series, 2019)
خضع حوالى 1138 مريضاً لاستئصال مرارة في مشفى الأسد الجامعي باللاذقية خلال فترة عشر سنوات (1997-2007)، 837 أنثى (73,55%) و301 ذكر (23,45%). وجد سرطان المرارة عند 17مريضاً (1,49%). شملت هذه الدراسة 17 مريضاً لديهم سرطانة مرارية، 13 أنثى (76,55%)، و4 ذكور (23,45%). العمر الوسطي وقت التشخيص 60,8 سنة. معدل إصابة الإناث إلى الذكور 3,25: 1. فكانت النتائج: الألم البطني أكثر الأعراض السريرية شيوعاً (94%). وجدت الحصيات المرارية في (88,2%). السرطانة الغدية أكثر الأشكال التشريحبة المرضية تواجداً (76,74%). التسمك في جدار المرارة، السليلات، الكتلة في سرير المرارة هي المعطيات الأكثر تقاطعاً بين التصوير بالأمواج فوق الصوتية والطبقي المحوري للبطن. يحضر معظم مرضى سرطان المرارة بمرحلة متقدمة من الداء (المرحلة III أو أكثر ). 1138 patients, 837 females (73.55%) and 301 males (23.45%), underwent cholecystectomy at Al-Assad University Hospital in Lattakia. GBC is found in 17 cases (1.49%). This study included 17 patients of GBC, 13 female (74.55%) and 4 males (23,45%). The mean age at diagnosis is 60.8 (41-75) years, with female to male ratio 3. 25: 1. The results are as follows: Abdominal pain was the most common symptom (94%). Gallstones are presented in 88.2%. Adenocarcinoma was the most common pathological type (76.74%). Thickwalled, polyps, and mass in gallbladder bed were the most common on both US and CT-scan. The majority of patients with GBC have advanced stage (STAGE III and above).